Standard Instrument Departure Design for Runway 30 at Airnav Indonesia Curug Sub Branch - Ramadhan, Muhammad Aditya; Praptiningsih, Nunuk; Putra, Gilang Trio (Kontribusia : Research Dissemination for Community Development, 2024)
This research aims to design a Standard Instrument Departure (SID) procedure for Runway 30 at Budiarto Airport, located in Curug, Tangerang Regency, Banten Province. This airport features a unique layout with two intersecting runways (cross runways). In addition to being used as a training airport by the Indonesian Aviation Polytechnic (PPIC), Budiarto Airport is frequently used for aircraft maintenance by PT. ANI. The airport is also in the process of extending Runway 30 from its original length of 1823 x 45 meters to 2150 x 45 meters. This extension is intended to offer a wider variety of aircraft services to operators, particularly for maintenance operations, and to attract business interest in launching domestic flight routes. One of the navigation aids at the airport includes the VOR BTO, which facilitates safe and efficient flight guidance. Using VOR, one of the procedures that can assist aircraft and ensure safety and efficiency is the implementation of a SID. The research methodology employed is Research and Development (R&D) Level One, involving data collection through literature review, documentation, and interviews with experts, including ATC personnel and flight procedure designers. The research process includes several stages: identifying potential issues, gathering information, designing the SID, expert validation, and drafting the SID in accordance with safety and efficiency standards, following ICAO Doc. 8168 guidelines. The results of the study, based on interviews with various stakeholders, indicate that the proposed SID design can enhance safety and efficiency at Budiarto Airport, Curug, Tangerang. It also aids ATC in maneuvering aircraft, thereby reducing communication requirements. The design has been validated by experts and deemed suitable for implementation. However, it should be noted that this design represents an initial study that could lead to further research and new insights, particularly concerning procedures once the SID is implemented. Additional research is needed, especially for VFR training aircraft from the aviation school at Budiarto.